BS EN 61108-6. Maritime navigation and radiocommunication equipment and systems. Global navigation satellite systems (GNSS). Part 6. Indian Regional Navigation Satellite System (IRNSS). Receiver equipment. Performance requirements, methods of testing and required test results (18th June 2021) - British Standards Institution,
No abstract available